Uji Aktivitas Antibakteri Ekstrak Etanol Bawang Putih (Allium Sativum L.) Terhadap Bakteri Penyebab Diare Vibrio Cholera ATCC 14033, Bacillus Cereus ATCC 11778 dan Escherichia Coli ATCC 25922 - Masayu Azizah; Renda Wella Sandri; Ema Ratna Sari Sari (Jurnal Kesehatan Saelmakers PERDANA, 2022)
The antibacterial activity of garlic (Allium sativum L.) ethanol extract has been tested against bacteria that cause diarrhea, this study aims to determine the antibacterial activity of garlic (Allium sativum L.) against test bacteria, namely Vibrio cholera ATCC 14033, Escherichia coli ATCC 25922 and Bacillus cereus ATCC 11778. . The test concentrations used were 60%, 50% and 40%, this type of research was experimental using the agar diffusion method. The results showed that the diameter of the inhibition zone formed in each of the test bacteria were Vibrio cholera ATCC 14033 10,53 mm, 8,46 mm, and 7,4 mm, Escherichia coli ATCC 25922 9,56 mm, 8,46 mm, and 7,36 mm and Bacillus cereus ATCC 11778 8,43 mm, 7,53 mm and 7,33 mm. The most optimal inhibitory power of garlic ethanol extract in inhibiting the growth of test bacteria was at a concentration of 60% against the bacterium Vibrio cholera ATCC 14033 with the resulting inhibition zone diameter of 10.53 mm and is included in the medium category.